2004
DOI: 10.1182/blood-2004-04-1390
|View full text |Cite
|
Sign up to set email alerts
|

Infant acute lymphoblastic leukemia with MLL gene rearrangements: outcome following intensive chemotherapy and hematopoietic stem cell transplantation

Abstract: Forty-four infants with acute lymphoblastic leukemia (ALL) characterized by MLL gene rearrangements were treated on a protocol of intensive chemotherapy followed by hematopoietic stem cell transplantation (HSCT) between November 1998 and June 2002. The remission induction rate was 91.0%, and the 3-year overall survival and event-free survival (EFS) rates, with 95% confidence intervals, were 58.2% (43.5%-72.9%) and 43.6% (28.5%-58.7%), respectively. Univariate analysis of EFS by presenting features indicated a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 44 publications
(37 reference statements)
4
71
0
5
Order By: Relevance
“…Infants with a rearranged MLL (MLL-R) gene received intensive chemotherapy followed by hematopoietic stem cell transplantation (HSCT), while those with a germline MLL gene were treated with standard intensive chemotherapy for ALL alone. This report updates findings published earlier [16][17][18] and extends the analysis to long-term side effects. By combining data from two studies with similar treatment strategies, we were able to analyze results for a relatively large cohort with this rare subtype of ALL.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Infants with a rearranged MLL (MLL-R) gene received intensive chemotherapy followed by hematopoietic stem cell transplantation (HSCT), while those with a germline MLL gene were treated with standard intensive chemotherapy for ALL alone. This report updates findings published earlier [16][17][18] and extends the analysis to long-term side effects. By combining data from two studies with similar treatment strategies, we were able to analyze results for a relatively large cohort with this rare subtype of ALL.…”
Section: Introductionsupporting
confidence: 86%
“…These studies accrued more than 80% of all Japanese infants with ALL over the 6-year enrollment period, based on results of a nationwide surveillance study. 17 The diagnosis of ALL was based on bone marrow morphology and cytochemical staining results. Each patient was evaluated with respect to the characteristics of the leukemic cells, including immunophenotype, cytogenetics and MLL gene status.…”
Section: Patientsmentioning
confidence: 99%
“…9,19 The TBI-containing conditioning regimen is widely used in HSCT for childhood ALL including the more aggressive infant form. 20,21 Although cyclophosphamide is more widely used along with TBI as a conditioning regimen, several reports have demonstrated the feasibility and efficacy of VP16 to replace cyclophosphamide. Jamieson et al 22 reported 61% EFS and 62% OS for children transplanted in CR2 after a conditioning regimen of FTBI (1320 cGY) and 60 mg/kg VP16 with accepted regimenrelated toxicity and TRM.…”
Section: Discussionmentioning
confidence: 99%
“…9 Results following SCT, from both related and unrelated donors, find that for infants in first remission, EFS ranges between 64 and 76%. [10][11][12] These infants underwent fully ablative conditioning, many receiving TBI, which increases the concern for late effects on growth and neurocognitive development. Although the risk of relapse with chemotherapy is high, it may be proposed to limit SCT to just those infants who relapse.…”
Section: Sct In First Remissionmentioning
confidence: 99%
“…Unfortunately, EFS is poor for infants transplanted after relapse, and it is unlikely to improve especially for patients coming for SCT after extremely aggressive primary chemotherapy. 10,11 Children with either B-cell or T-cell ALL and specific highrisk features, for example, marked leukocytosis at presentation, hypodiploid karyotype, inadequate response to induction chemotherapy or persistent minimal residual disease, have experienced a high failure rate on contemporary chemotherapy regimens. 3 If an HLA-matched related donor is available, SCT in first remission may be a more effective approach for these very high-risk subsets.…”
Section: Sct In First Remissionmentioning
confidence: 99%